2007
DOI: 10.1007/s12026-007-8011-z
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in differentiation and function of dendritic cells

Abstract: Hematopoietic stem cells give rise to multiple lineages of cells. This process is governed by a tightly controlled signaling network regulated by cytokines and a direct cell-cell. Notch signaling represents one of the major pathways activated during direct interaction between hematopoietic progenitor cells and bone marrow stroma. A critical role of Notch signaling in differentiation of T and B lymphocytes has now been established. Until recently, the role of Notch signaling in the development of myeloid cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 108 publications
(128 reference statements)
1
28
0
Order By: Relevance
“…Maturation of Human DCs-The maturation of DCs often involves the spectrum of cellular signaling events, including TLR2-dependent activation of NOTCH signaling, which is suggested to play an important role in critical cell fate decisions during DC maturation and subsequent priming of effector T cell responses (37,38). In this regard, we and others have previously shown that TLR2 stimulation leads to up-regulation of NOTCH1 and activation of the NOTCH1 signaling pathway by inducing the formation of a cleavage product of NOTCH1 (NICD) as well as robust activation of Jagged1 expression, a NOTCH1 receptor ligand (39 -44).…”
Section: Notch1-pi3k Signaling Dynamics Integrated Into Signaling Cohmentioning
confidence: 99%
“…Maturation of Human DCs-The maturation of DCs often involves the spectrum of cellular signaling events, including TLR2-dependent activation of NOTCH signaling, which is suggested to play an important role in critical cell fate decisions during DC maturation and subsequent priming of effector T cell responses (37,38). In this regard, we and others have previously shown that TLR2 stimulation leads to up-regulation of NOTCH1 and activation of the NOTCH1 signaling pathway by inducing the formation of a cleavage product of NOTCH1 (NICD) as well as robust activation of Jagged1 expression, a NOTCH1 receptor ligand (39 -44).…”
Section: Notch1-pi3k Signaling Dynamics Integrated Into Signaling Cohmentioning
confidence: 99%
“…Notch1 expression and downstream signaling play crucial roles in immune cell differentiation and development (42,43). Although Notch1 is abundantly expressed in DCs, its role in DC crosspriming remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Both canonical Wnt and Notch signaling pathway is indispensable for stem and progenitor cell fate determination and subsequent differentiation during embryonic development and adult life (42)(43)(44)(45)(46). These two pathways are reciprocally regulated.…”
Section: Discussionmentioning
confidence: 99%